N-acetylgalatosamine-Mediated Regulation of the aga Operon by AgaR in Streptococcus pneumoniae - Afzal, Muhammad; Shafeeq, Sulman; Ahmed, Hifza; Kuipers, Oscar P. (Frontiers in Cellular and Infection Microbiology, 2016)
Here, we analyze the transcriptomic response of Streptococcus pneumoniae D39 to N-acetylgalactosamine (NAGa). Transcriptome comparison of S. pneumoniae D39 grown NAGaM17 (0.5% NAGa + M17) to that grown in GM17 (0.5% Glucose + M17) revealed the elevated expression of various carbon metabolic genes/operons, including a PTS operon (denoted here as the aga operon), which is putatively involved in NAGa transport and utilization, in the presence of NAGa. We further studied the role of a GntR-family transcriptional regulator (denoted here as AgaR) in the regulation of aga operon. Our transcriptome and RT-PCR data suggest the role of AgaR as a transcriptional repressor of the aga operon. We predicted a 20-bp operator site of AagR (5’- ATAATTAATATAACAACAAA -3’) in the promoter region of the aga operon (PbgaC), which was further verified by mutating the AgaR operator site in the respective promoter. The role of CcpA in the additional regulation of the aga operon was elucidated by further transcriptome analyses and confirmed by quantitative RT-PCR.